Assessment of GreenComp learning in the training of education professionals - Martínez-Agut, M. Pilar; Monzó-Martínez, Anna; Ortiz-Cermeño, Eva (Frontiers in Education, 2025)
IntroductionThe European Green Pact outlines various actions to promote awareness and learning about environmental sustainability. It highlights the European Framework of Competences for Sustainability (GreenComp), which is to be introduced in educational programs. Thus, students develop knowledge, skills, and attitudes that promote thinking, planning, and acting with empathy, responsibility, and care for the planet and their own health. This framework comprises 12 competencies located in four interrelated areas: “embodying sustainability values,” “assuming the complexity of sustainability,” “imagining sustainable futures,” and “acting for sustainability.” This research analyzes the competencies that undergraduate and master’s degree students at the University of Murcia and the University of Valencia claim to possess in the field of sustainable development (477 participants).MethodsThe methodology employed was descriptive-comparative and quantitative, utilizing an ad hoc questionnaire.ResultsThe results show that the competencies presented by the students in the experimental and control groups differed at the end of the four months. In particular, the intervention showed a positive effect in the experimental group (EG) in terms of gender and degree taken.DiscussionThese results highlight the need to incorporate ESD from the initial training stage. The application of active techniques and the use of frameworks such as GreenComp offer specific tools that help students develop practical skills and a critical perspective on sustainability.